Pengaruh Model Picture and Picture terhadap Minat Belajar pada Pembelajaran Tematik Siswa Kelas III SD Negeri Banjarharjo Kabupaten Sleman - Cintya Anggun Kirani; Annisa Adelia; Anggita Septiarini; Mia Mince Tagi; Mahilda Dea Komalasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Education aims to foster an active learning environment where students can develop their full potential. One innovative approach to enhance student engagement is the Picture and Picture learning model, which has been shown to increase students’ interest—a crucial factor in successful learning. Without interest, students often become passive participants. This study investigates the effect of the Picture and Picture model on the learning interest of third-grade students at Banjarharjo State Elementary School, Sleman, during thematic instruction on the topic “Preserving Nature.” Employing a one-group pre-experimental design, the research involved administering pre-tests and post-tests using a questionnaire to assess changes in students' learning interest. The findings indicate a significant improvement: the average interest score rose from 32.94 (pre-test) to 37.36 (post-test). This increase suggests that students became more engaged and interested in the thematic learning content after the model was applied. Therefore, the study concludes that the Picture and Picture model positively and significantly influences students’ interest in learning, particularly within the theme of “Preserving Nature.”